الوقف الإسلامي: دراسة في الأركان وطرق التعامل معه = Islamic endowment: study of its pillars and methods of dealing - Abdul Manas, Shayuthy; Abdullah, Ismail (Department of Fiqh and Usul Fiqh, Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Anybody who studies on the conditions of waqf (endowment) in the Islamic world will discover various views in dealing with it. In order to fulfil the ultimate purposes behind waqf and to meet the needs of people, some restrict its function solely on real estate; neglecting many other aspects of waqf, which eventually leads to deprivation of its benefits. On the other hand, some expand its function through several means; yet those means are merely based on experiment and not immune from risks. Another view shows hesitation to maintain any of these views. The aim of this study is to highlight the pillars of waqf and ways of dealing with it as to enable real growth, development and investment of waqf in accordance with the Shari'ah. Thus, the civilizational advancement of the ummah would be achieved by fulfilling the needs of the people and helping them through waqf. The two researchers will rely on the analytical descriptive approach in their work. They will use the descriptive approach in determining the meaning of waqf and its legitimacy, and the analytical method in defining its structure and methods of dealing. It is understood that there are four pillars of waqf; namely, the one who endows, the endowment, the one who is entitled for endowment, and statements related to endowment. It is incumbent to note that conditions for each pillar should be fulfilled to achieve the purposes of endowment. Besides, it is possible to deduce the types of waqf based on the pillars through multiple considerations. With regards to the precise understanding of waqf, it could be inferred as familial endowment (al-waqf al-ahlī), and public endowment. While with regards to the property of endowment (al-mal al-mawqūf), it is understood as real estate, transferable endowment, and currency endowment. At the same time, the most effective way in dealing with waqf could be managed in three aspects; al-tasyīr, al-istismār, and al-istibdāl.